Relationship Type and Sexual Precedence: Their Associations With Characteristics of Sexual Assault Perpetrators and Incidents - Wegner, Rhiana (Violence Against Women, 2014)
Although most sexual assaults are committed by men who know their victims, few researchers have considered how characteristics of perpetrators and incidents differ depending on the victim–perpetrator relationship. This study addresses this gap with a community sample of 204 men who reported committing a sexually aggressive act in an audio computer-assisted self-interview. 2 (Relationship Type: Committed vs. Casual) × 2 (Sexual Precedence: Yes vs. No) ANOVAs revealed significant main effects of relationship type and sexual precedence associated with individual difference and incident characteristics. These findings demonstrate the importance of developing theories and prevention programs tailored for different relationship contexts.